PENGARUH RETRIBUSI PELAYANAN PASAR TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA METRO-LAMPUNG - Suwarto; Ali, Karnila (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
In an effort to create regional independence, Regional Original Revenue is a very important factor, where PAD is the source of funds from the region itself. Government financing in carrying out government and development tasks always requires a reliable source of revenue. The purpose of this study was to determine the effectiveness of market service retribution in Metro City in 2019. To determine the contribution of market service retribution to Metro City's local revenue.This type of research is carried out using quantitative methods. Research is carried out at the Metro City Government or Metro City Revenue Service. The data obtained from the research results were then analyzed by quantitative descriptive analysis.Based on the results of research and data analysis that has been carried out, it can be concluded that: Revenue from market service retribution is effective in increasing Metro City PAD from 2019-2020. The market service levy has a large contribution to Metro City's Original Regional Revenue (PAD) from 2019 to 2020.